The Correlation Between Absolute Lymphocyte Count and Quantitative CRP Level Related to Disease Severity in COVID-19 Patients at RSUP dr. Mohammad Hoesin Palembang - Nadia Karimah Amalia Zulfadli; Zen Ahmad; Mgs Irsan Saleh; Ahmad Rasyid (Fakultas Kedokteran Universitas Sriwijaya, 2021)
COVID-19 is a contagious acute respiratory disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus. Changes in some laboratory markers such as absolute lymphocyte count and quantitative CRP in COVID-19 can be associated with the course and clinical phases of the patient whose results can be useful in grading and predicting the severity of COVID-19 disease. This study aims to determine the correlation between absolute lymphocyte count and quantitative CRP on the severity of COVID-19. This study was an observational correlative analytic study with a cross sectional design. The research was conducted in all COVID-19 treatment isolation wards at RSMH Palembang from March 2021 to April 2021 with the research subjects being patients with confirmed cases of COVID-19 with various degrees of disease. Routine blood tests of absolute lymphocyte counts and quantitative CRP were performed at the Clinical Pathology Laboratory of RSMH Palembang. The statistical analysis of the correlation test with Spearman for numerical data was not normally distributed, and Gamma for categorical ordinal data was followed by a regression test to determine the prognostic value of the two parameters. Samples obtained were 83 patients, namely 24 patients (28.9%) mild degree, 40 patients (48.2%) moderate degree, 10 patients (12%) severe degree and 9 patients (10.8%) critical degree. The correlation between the absolute lymphocyte count and quantitative CRP obtained the correlation coefficient value r = – 0.525. The correlation between the absolute lymphocyte count and the degree of COVID-19 disease obtained a correlation coefficient of r = – 0.605, while the correlation between the quantitative CRP value and the degree of disease was obtained r = 0.875. Based on the prognostic test, the absolute lymphocyte count (cutoff point of 1,157 cells / mm3) was obtained with a sensitivity of 68.4% and a specificity of 68.75%. Meanwhile, quantitative CRP with a cutoff point of 77.5 mg/L obtained a sensitivity of 89.4% and a specificity of 89%. The absolute lymphocyte count has a strong negative correlation with the quantitative CRP value and the disease degree in COVID-19, while the quantitative CRP value has a positive correlation with a very strong degree. Thus these two parameters can be used as predictors of disease severity, however, the quantitative CRP value can be an independent prognostic marker or a single predictor of the severity of COVID-19 disease.